2016
DOI: 10.14254/2071-789x.2016/9-4/8
|View full text |Cite
|
Sign up to set email alerts
|

From Financial Measures to Strategic Performance Measurement System and Corporate Sustainability: Empirical Evidence from Slovakia

Abstract: Today's world brings in many new pulses for enterprises not to focus on well established performance management tools used in the past. There is an obvious need to use new methods of performance management within strategic-oriented management. A good example here is also the concept of corporate sustainability. This concept is focused on company's performance in the long term, whereby the company essentially follows not only profitability, but also takes into account the process and results of all activities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…These have brought positive results to the discussion by analyzing the variables through different points of view and the use of different methods. Yet, other studies sought to explore the effects of sustainability disclosures over financial performance in contexts such as construction companies (Siew, Balatbat, & Carmichael, 2013), the relationship between sustainability disclosure and its effects on a firm's financial performance (Kasbun, Teh, & Ong, 2017;Said, Theng, Senik, Yusri, & San, 2015), sustainability reporting quality and its relationship with corporate financial performance (Ching, Gerab, & Toste, 2017), CSR disclosure in the textile industry (Krause, 2018), evaluating the impact of sustainable strategies on financial performance (Siminica, Craciun, & Dinu, 2015), determining whether the quality of the sustainability disclosures had an influence on the financial outcomes of companies listed in the ISE (Ching et al, 2017), determining the effects of the performance measuring parameters on the overall outcome of a business and on the index composed of sustainable development to determine its impact in Slovakian companies (Rajnoha, Lesníková, & Koraus, 2016), and describing the connection between financial results and sustainability levels (Wagner & Blom, 2011), bringing either positive, negative, or inconclusive results.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…These have brought positive results to the discussion by analyzing the variables through different points of view and the use of different methods. Yet, other studies sought to explore the effects of sustainability disclosures over financial performance in contexts such as construction companies (Siew, Balatbat, & Carmichael, 2013), the relationship between sustainability disclosure and its effects on a firm's financial performance (Kasbun, Teh, & Ong, 2017;Said, Theng, Senik, Yusri, & San, 2015), sustainability reporting quality and its relationship with corporate financial performance (Ching, Gerab, & Toste, 2017), CSR disclosure in the textile industry (Krause, 2018), evaluating the impact of sustainable strategies on financial performance (Siminica, Craciun, & Dinu, 2015), determining whether the quality of the sustainability disclosures had an influence on the financial outcomes of companies listed in the ISE (Ching et al, 2017), determining the effects of the performance measuring parameters on the overall outcome of a business and on the index composed of sustainable development to determine its impact in Slovakian companies (Rajnoha, Lesníková, & Koraus, 2016), and describing the connection between financial results and sustainability levels (Wagner & Blom, 2011), bringing either positive, negative, or inconclusive results.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…According to Musa et al (2016) it is also necessary to look for financial support mechanisms dedicated to supporting the creation and growth of small and medium-sized enterprises in the era of globalized economy. Rajnoha et al (2016) emphasize that financial questions should be part of the complex financial management in order to maintain competitiveness. Such a managerial attitude is also supported by (Rogalska, 2014) and (Pellesova & Kajzar, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The issue of human capital is discussed by many authors in terms of the theory of human capital [13][14] [15], social capital [16], marco-economy [5][13] [14] or micro-economy [13] [17] as well as other approaches [8]. The common feature of these studies is the fact that human capital represents a source of progress and economic growth, plays an important role in the development of each and every enterprise.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the reality in companies is different, as proved by the results of the survey carried out by Accenture [11] which showed that many companies do not even attempt to measure their investment in human capital. Despite the fact that the topic of human capital is very important and widely discussed in Slovakia authors [12] [13] and others deal with this issue mostly in terms of company's performance taking into account intellectual capital or innovations. However, there is an obvious absence of research focused on measuring investment in human capital and its reporting.…”
Section: Introductionmentioning
confidence: 99%